Validity and reliability of a test battery to assess change of directions with ball dribbling in para-footballers with cerebral palsy - Daniel, L. F.; Reine, R.; Gorla, J. I.; Bastos, T.; Roldan, A. (Brain Sciences, 2020)
The purpose of this study was to evaluate the content and construct validity and between-sessions reliability of four agility tests requiring ball dribbling in football players with cerebral palsy (CP) with implications for classification and training. A sample of 35 football players with CP from three different countries took part in the study. They performed four tests in two sessions 72 h apart: i) 20 m in a straight line, ii) forward slalom with short changes of direction, iii) forward slalom with wide changes of direction and iv) square course. The Kappa coefficient was used to test content validity, obtaining moderate to almost perfect agreement results. Construct validity was also demonstrated with very large to almost perfect correlations between tests and sessions. Good reliability was found using intra-class coefficients (>0.86), standard error of measurement (<10.8%) and Cronbach´s alpha (>0.86). The comparisons between CP profiles (i.e. sport classes) demonstrated that those with mild impairment performed faster, and those with impairment of ataxia and dyskinesia performed worse. The four tests could have applications in classification, but may also be applied by the CP football coaches to improve athlete agility and football skills.